Non-invasive monitoring of Aspergillus infections in chronic lung disease patients: a combined serology and HRCT imaging approach - Zhang, Rong; Yang, Lei; Fang, Hong; Xie, Qian; Tang, Huan; Chen, Lin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundDiagnosing Aspergillus infections in patients with chronic pulmonary diseases is challenging, particularly in settings where invasive diagnostic tools are limited. This study explores a non-invasive diagnostic approach, combining serological tests and high-resolution computed tomography (HRCT) imaging, to identify patients who may need further invasive evaluation for Aspergillus infection.MethodsThis retrospective study included patients with chronic pulmonary diseases from regional centers who experienced acute exacerbations that did not respond to antibacterial therapy, had positive sputum cultures for Aspergillus species, and lacked typical invasive radiological features on HRCT. Patients were classified based on clinical data, HRCT imaging, and serological markers (IgG, IgM, galactomannan) to distinguish between Aspergillus colonization and clinically diagnosed active infection.ResultsOf the 2,731 patients assessed, 209 met the study criteria: 112 were identified with Aspergillus colonization, and 97 with clinically diagnosed Aspergillus infection. Patients with active infection had significantly higher Aspergillus -specific IgG levels (median 185.47 IU/mL vs. 59.96 IU/mL, p<0.001) and higher galactomannan indices, especially those with invasive infection (p<0.001). HRCT scores were strongly correlated with the risk of infection. The combination of IgG levels and HRCT scores achieved an AUC (area under the curve) of 0.9 for differentiating infection from colonization and 0.74 for distinguishing different types of Aspergillus infections.ConclusionThis study supports the use of a non-invasive diagnostic approach, combining serological testing and HRCT imaging, to identify patients with chronic lung diseases who have positive sputum cultures for Aspergillus and are highly suspected of active infection, such as invasive pulmonary aspergillosis and chronic pulmonary aspergillosis, for further invasive diagnostic evaluation. This method is particularly useful in patients who experience frequent acute exacerbations and are unwilling or unable to undergo invasive diagnostic procedures, helping clinicians identify those who really require further definitive evaluation and thereby reducing unnecessary antifungal treatment.Clinical trial registrationhttps://www.clinicaltrials.gov, identifier NCT06379568.